2019
DOI: 10.1007/s10338-019-00112-8
|View full text |Cite
|
Sign up to set email alerts
|

Review of Soft Linear Actuator and the Design of a Dielectric Elastomer Linear Actuator

Abstract: Natural muscle provides excellent motilities for animals. As the basic unit of the muscle system, the skeletal muscle fibers function as a soft linear actuator. Inspired by the muscle fibers, researchers have developed various soft active devices with linear actuation. This paper reviews several soft linear actuators, such as the dielectric elastomer, thermal responsive hydrogels, pneumatic artificial muscle, and conducting polymers. The actuation mechanisms and performances of these soft linear actuators are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(16 citation statements)
references
References 88 publications
0
16
0
Order By: Relevance
“…Besides, the subharmonic resonance peak also shifts toward right with the increasing voltage. Due to the nonlinear coupling, modes (1, 1), (1,3) and (2, 1) present the additional branches in the frequency region corresponding to the local peak of mode (1,2). Comparing the results in Cases 1 and 2, it is found that the combined voltage excitation composed of both the AC and DC components can stimulate the nonlinear dynamic response of the soft cantilever plate more effectively.…”
Section: Nonlinear Dynamics Of the Soft Sandwich Cantilever Platementioning
confidence: 92%
See 1 more Smart Citation
“…Besides, the subharmonic resonance peak also shifts toward right with the increasing voltage. Due to the nonlinear coupling, modes (1, 1), (1,3) and (2, 1) present the additional branches in the frequency region corresponding to the local peak of mode (1,2). Comparing the results in Cases 1 and 2, it is found that the combined voltage excitation composed of both the AC and DC components can stimulate the nonlinear dynamic response of the soft cantilever plate more effectively.…”
Section: Nonlinear Dynamics Of the Soft Sandwich Cantilever Platementioning
confidence: 92%
“…Generally, DEs are regarded to be a class of typical soft materials whose mechanical deformation behaviors are similar to hyperelastic materials. Due to their outstanding characteristics, including the fast response, high energy density, low noise, light weight, marvelous flexibility, excellent inherent compliance, as well as low cost, dielectric elastomer actuators (DEAs) have attracted considerable interest, and become a promising soft actuator technology for bioinspired robotics [1][2][3] . As an important source of inspiration for the soft actuator designer, the bird wings and fin structures of aquatic animals can be modeled by cantilever plates which are widely applied in the engineering filed, such as airplane wings, satellite solar panels and turbine blades [4][5][6][7][8] .…”
Section: Introductionmentioning
confidence: 99%
“…So far, a bulk of the studies conducted provide the actuations mostly in term of percentage, i.e., 10%, 40%, 100%, 200%; however, for specific applications like in soft robotics or even in artificial muscles and other biomimetic devices, each component requires a specific amount of actuating force [ 5 , 14 ]. Therefore, we propose the actuation in terms of relative force which has also been regarded as an ultimate motivation of the present study.…”
Section: Introductionmentioning
confidence: 99%
“…Lü et al [9] theoretically derived the output power of ultrathin flexible piezoelectric energy harvesters under a variety of excitation modes. Cao et al [10] reviewed the actuation mechanisms and performances of representative soft linear actuators made from smart materials such as dielectric elastomers, thermal responsive hydrogels, pneumatic artificial muscles and conducting polymers. Ma et al [11] designed an experimental setup to quantify the out-of-plane vibrations and different response modes of a circular dielectric elastomer actuator.…”
mentioning
confidence: 99%